2018
DOI: 10.1002/ana.25344
|View full text |Cite
|
Sign up to set email alerts
|

Relative neuron loss in hippocampal sclerosis of aging and Alzheimer's disease

Abstract: Objective: To characterize the pattern of neuron loss in hippocampal sclerosis of aging (HS-Aging) and age-related diseases and to evaluate its contribution to cognitive impairment in the elderly. Methods: Participants (n = 1,361) came from longitudinal observational studies of aging at the Knight Alzheimer Disease Research Center, Washington University, Saint Louis, Missouri, USA. Relative neuron loss in the hippocampus of HS-Aging was measured using unbiased stereological methods. Transactive response DNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…11 In the current cohort, TDP-43 pathology was present at least to a mild extent in 37% of cases, which agrees with the prevalence of TDP-43 in previous studies, ranging between 33% and 52% in cases with AD pathology. 40,[42][43][44] Also consistent with these previous studies, the regional distribution of TDP-43 inclusions in the current sample was almost exclusively focused on MTL regions, including hippocampus, entorhinal cortex, and amygdala, and only 6 patients had neocortical TDP-43 inclusions in addition to MTL involvement. These data underscore the strong association of regional distribution of TDP-43 inclusions with the regional pattern of brain atrophy, consistent with previous reports on amygdala and hippocampal involvement with TDP-43 pathology 45 and the current discussion on limbic predominant TDP-43 pathology in older individuals that has recently been termed limbic-predominant age-related TDP-43 encephalopathy (LATE).…”
Section: Discussionsupporting
confidence: 90%
“…11 In the current cohort, TDP-43 pathology was present at least to a mild extent in 37% of cases, which agrees with the prevalence of TDP-43 in previous studies, ranging between 33% and 52% in cases with AD pathology. 40,[42][43][44] Also consistent with these previous studies, the regional distribution of TDP-43 inclusions in the current sample was almost exclusively focused on MTL regions, including hippocampus, entorhinal cortex, and amygdala, and only 6 patients had neocortical TDP-43 inclusions in addition to MTL involvement. These data underscore the strong association of regional distribution of TDP-43 inclusions with the regional pattern of brain atrophy, consistent with previous reports on amygdala and hippocampal involvement with TDP-43 pathology 45 and the current discussion on limbic predominant TDP-43 pathology in older individuals that has recently been termed limbic-predominant age-related TDP-43 encephalopathy (LATE).…”
Section: Discussionsupporting
confidence: 90%
“…With that said, in our experience, the frequency of TDP-43 in PART is significantly lower than the frequency in Alzheimer's disease. In Alzheimer's disease, we and others have found frequencies of TDP-43 deposition in the range of 50%-70%, when the amygdala is screened [11,42,47,48]. In fact, one study reported a frequency even greater than 70% in Alzheimer's disease [49].…”
Section: Discussionmentioning
confidence: 77%
“…The hippocampal lesions in the CA1 area more likely cause dementia with deficits in memory. Reducing lesions in this area of the brain is conducive to improving cognitive function (Ihara et al, 2018). Thus, improved cognitive function following DCA treatment can be partly attributed to reduced hippocampal damage.…”
Section: Discussionmentioning
confidence: 99%